Practicality of biology learning devices based on socioscientific issues integrated with the Sasirangan verse digital application - Siti Ramdiah; Ria Mayasari; A. Abidinsyah; Dini Arini (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Rapid environmental degradation and the growing complexity of socioscientific problems demand science education that connects scientific literacy with ethical, cultural, and local contexts. However, classroom practices often remain content-centered, lacking contextual materials that link science concepts with students’ lived experiences. This gap limits students’ ability to reason uucritically and make informed decisions on real-world issues. To address this challenge, this study evaluates the practicality of a Socioscientific Issues (SSI)-based biology learning package integrated with the Sasirangan Verse digital application—a platform designed to embed local cultural wisdom from South Kalimantan into science learning. A quantitative design was employed, involving 30 high school biology teachers who assessed practicality using a four-point Likert scale across four dimensions: relevance, effectiveness, engagement, and curriculum alignment. Complementary data were collected from 231 students whose cognitive achievements (C2–C6) were analyzed using a one-way ANOVA. Results showed that all items scored above 3.0, with an overall mean of 3.53 (PSM = 88.25%), categorized as highly practical. The effectiveness dimension obtained the highest mean, followed by engagement, relevance, and standard alignment. The instrument exhibited strong reliability (Cronbach’s α = 0.886). A one-sample t-test against the benchmark value of 3.0 was significant (p < 0.001), and the experimental group significantly outperformed the control group (F(1,229) = 17.184, p < 0.001, η² = 0.07), indicating a medium effect size on students’ cognitive outcomes. These findings suggest that the SSI-based learning device integrated with Sasirangan Verse is both practical for teachers and effective in enhancing students’ cognitive performance when implemented as a continuous, contextually grounded learning sequence. The study underscores the importance of supporting implementation through curriculum alignment, Bloom-based rubrics, and short professional development programs to foster wider adoption in secondary biology education.